Life as Primary Text: English Classrooms as Sites for Soulful Learning - Vajra Watson (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Poet mentors help at-risk students connect their life experiences with literature, demonstrating a pedagogy that incorporates art, science, and the human soul.